Pakistan : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2004)
To stimulate private sector credit expansions in Pakistan, the monetary policy has been accommodative while financial sector reforms have brought about a lowering of intermediation costs and bank spreads. Consequently, the weighted average lending rates have declined from 14.6 percent in June 1999 to 7.58 percent in June 2003. Likewise, the weighted average 6-month T-bills yield has declined from 10.60 percent in June 1999 to 1.66 percent in June 2003. Considerable progress has been made in terms of creating a legal and institutional framework.